Pelatihan Penyusunan Laporan Keuangan bagi Siswa Paket C Pusat Kegiatan Belajar Masyarakat (PKBM) Sahabat Cendekia Batam - Fadlilah, Andi Hidayatul; Mulyadi, Mulyadi; Mustika, Ita Mustika; Khadijah, Khadijah; Richmayati, Maya (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
This community service activity aims to provide basic skills and knowledge in managing finances and preparing simple financial reports with the hope that Package C students can acquire basic skills and knowledge in managing finances effectively and efficiently. This community service focuses on pursuing Package C (equivalent to high school) students. The partner's problem is that there are still many Package C students who have not been able to compile simple financial reports. The method of implementing community service activities is carried out in several stages. The first stage is the preparation stage through observation and interviews. The second stage is the implementation of activities in the form of technical guidance which is carried out by presenting material, practice, and discussion. The third stage is evaluation. The implementation of this activity was carried out for two days, namely on 04 - 05 March 2023. Through this community service activity, it is hoped that the participants will have better skills and knowledge in the field of accounting so that they will be ready to enter the world of work and be able to manage their finances when entering the business world.